2012
DOI: 10.1093/carcin/bgs027
|View full text |Cite
|
Sign up to set email alerts
|

Id-1 and the p65 subunit of NF-κB promote migration of nasopharyngeal carcinoma cells and are correlated with poor prognosis

Abstract: Inhibitor of differentiation (Id)-1 and nuclear factor-kappa B (NF-κB) have been detected in many malignant tumors, and their presence has been correlated with the metastatic potential of these tumors. This study was undertaken to investigate the prognostic significance of the expression of Id-1 and the p65 subunit of NF-κB (NF-κB/p65) and the proteins' roles in the invasion process of nasopharyngeal carcinoma (NPC) cells. The messenger RNA (mRNA) and protein levels of Id-1 and NF-κB/p65 in normal nasopharynge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 40 publications
4
43
0
Order By: Relevance
“…The medium from each well was collected and freeze dried. The dried medium was dissolved in 100 μl H 2 O and protein concentration was measured (Sun et al, 2012). Equal amounts of protein from each sample were then electrophoresed in a 10% SDS-PAGE containing 0.1% (w/v) gelatin.…”
Section: Gelatin Zymography Assaymentioning
confidence: 99%
“…The medium from each well was collected and freeze dried. The dried medium was dissolved in 100 μl H 2 O and protein concentration was measured (Sun et al, 2012). Equal amounts of protein from each sample were then electrophoresed in a 10% SDS-PAGE containing 0.1% (w/v) gelatin.…”
Section: Gelatin Zymography Assaymentioning
confidence: 99%
“…Accumulating evidence has confirmed that ID1 is upregulated in several types of tumors including breast, prostate, lung, gastric, esophageal and colorectal adenocarcinoma (12,13). This increase in ID1 expression appears to be crucial for growth grades, invasive properties and subsequently a poor clinical outcome (13)(14)(15)(16)(17)(18). Evidence also indicates that expression of ID proteins, including ID1, correlates with the p53 level and the mitotic index in colorectal tumors (19,20).…”
Section: Introductionmentioning
confidence: 97%
“…PCR reactions were performed using Power SYBR Green PCR Master Mix and 7500 Fast Real-Time PCR System (Applied Biosystems, CA, USA). Primer sequences specific for the NFκB /p65 (No: NM_021975.3) are : Fwd: 5'-ATCTGCCGAGTGAACCGAAACT-3'; and Rev: 5'-CCAGCCTGGTCCCGTGAAA-3' (Sun W et al, 2012); β-actin (No:NM_001101.3): Fwd: 5'-TGGCATTGCCGACAGGATGCAGAA-3', Rev:5'-CTCGTCATACTCCTGCTTGCTGAT -3'. β-actin primers were used as an internal control.…”
Section: Laboratory Investigations Includedmentioning
confidence: 99%